City of likes : a novel - Mollen, Jenny, 1979- (Nacelle Books, 2022)
"Megan Chernoff is a talented but unemployed copywriter in an identity crisis after the birth of her second child. Seeking a fresh start, she and her family move to New York City, where she meets Daphne Cole-a gorgeous, stylish, well-known momfluencer. To Meg's surprise and delight, Daphne shows an inordinate amount of interest in Meg, showering her with compliments, attention, gifts, and all the perks that come with having a massive digital platform. Before she knows it, Meg finds herself immersed in Daphne's world-hobnobbing at exclusive power mama supper clubs, partaking in fancy wellness rituals, and reveling in the external validation she gets from her followers who grow daily by the thousands. Her friendship with Daphne, as well as the world she's been granted access to, is intoxicating and all-consuming. But is it authentic? When Meg realizes she's losing track of what matters most-her relationship with her sons and her husband-the deep cracks in Daphne's carefully curated façade are finally exposed. It's up to Meg to find her way back to her real life. But first she must determine what "real" even means."-- Amazon.com.